2020
DOI: 10.4314/tjpr.v19i7.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous ginger (Zingiber officinale) extract on sperm quality and haematology in lead acetate-treated male albino rats

Abstract: Purpose: To evaluate the ameliorative effects of aqueous ginger extract on sperm quality and haematology in lead acetate-treated male albino rats.Methods: Twenty-four male albino rats used for this study were randomly assigned to four groups (n = 6). Group 1 was the normal control. Lead acetate (4 mg/kg) was given to group 2 for 6 weeks. Lead acetate (4 mg/kg) and ginger (300 mg/kg) were given to group 4 simultaneously for 6  weeks, while group 4 was given lead acetate (4 mg/kg) for 6 weeks, and then, ginger (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…These data suggested that ginger may help maintain healthy sperm parameters (Al-Kashef 2021). Recently, ginger extract had potential to improve semen quality and quantity in lead acetate-treated male rats (Banihani 2018; Odo et al 2020). Moreover, Morakinyo et al (2008) found that GE was significantly increase the relative weight of the rat testis as well as serum testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggested that ginger may help maintain healthy sperm parameters (Al-Kashef 2021). Recently, ginger extract had potential to improve semen quality and quantity in lead acetate-treated male rats (Banihani 2018; Odo et al 2020). Moreover, Morakinyo et al (2008) found that GE was significantly increase the relative weight of the rat testis as well as serum testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Banihani (2018) attributed the possible mechanisms of improved male fertility by ginger extract due to its ability to increase testosterone production, reduce oxidative stress, enhance the activity of antioxidant enzymes, and normalize blood glucose levels. Ginger extract has potential to improve semen quality and quantity in lead acetate-treated male rats (Odo et al 2020). The purpose of this study was to see how coadministration of GE and Vit.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the treatment increased the viability of TM3 and TM4 cells (Rafiee et al, 2019). Odo et al (2020) evaluated the preventive effect of ginger extract against lead acetate on sperm quality and haematology in male rats. In this study, the simultaneous ingestion of lead acetate with aqueous ginger extract (300 mg/kg) for 6 weeks induced a significant increase in the spermatozoa parameters (viability and motility), and the production of red blood cells.…”
Section: Protective Effects Against Male Infertilitymentioning
confidence: 99%
“…Also, the level of white blood cells was significantly reduced. The ameliorative impact of ginger on spermatozoa parameters may be associated with its antioxidant properties, and the presence of vitamin C (Odo et al, 2020).…”
Section: Protective Effects Against Male Infertilitymentioning
confidence: 99%
“…Many studies revealed that ginger has various activities such as immune-modulatory, antioxidant and anti-apoptosis (Hosseinzadeh et al, 2017). Zingiber has a constructive influence on improved sperm numbers, motility, testosterone levels, and reproductive activities in rats (Odo et al, 2020;Seif et al, 2021). Consequently, this study has been conducted out to assess the defending effects of the ethanolic extract of ginger against the testicular alterations produced by MSG administration on male albino rats.…”
Section: Introductionmentioning
confidence: 99%